Conductivity-permittivity relations in oxygen deficient CaCu3Ti4O12. Issue 11 (1st August 2018) - Luo, X.J.; Bärner, K.; Zhang, Y.T.; Gao, T.; Yang, C.P.; Liu, Y.S.
Abstract: The correlation between conductance, capacitance and oxygen content is discussed in the colossal dielectric permittivity perovskite oxide CaCu3 Ti4 O12 . We found an unusual positive conductivity-permittivity relation which is very sensitive to the oxygen content. In particular, we ascribe the oxygen content sensitivity of both the capacitance and the conductance to a repositioning of charges on oxygen vacancy related defects and/or on the migration of the defects themselves. We find that in the charge repositioning process a Jonscher type of global conduction is accompanied by a Debye-type local electronic relaxation in and between the boundaries of a specific grain. A closer investigation of these processes suggest that the local polaronic relaxation of charges on oxygen vacancy related defects is mainly responsible for the large dielectric constant of CaCu3 Ti4 O12 and also for the ac conduction at low to medium temperatures.